ANALISA PENGARUH DAYA LASER MARKING TERHADAP LAJU KOROSI AISI 304 STAINLESS STEEL - Wijayanto, Hendi Lilih; Muh. Azis albar J; Yusdianto, Yusdianto; Setiawan, Angga Tegar; Putra, Aditya Perdana (Universitas Nahdlatul Ulama Blitar, 2024)
The purpose of this study is to determine the effect of power on marking quality, namely groove geometry and marking visibility and corrosion rate on AISI 304 stainless steel fiber laser marking material in corrosive seawater media. This is important because based on the results of the analysis report from the information department, the results of fork and spoon products experience corrosion, especially in the area of laser marking results. In this study, the surface of AISI 304 stainless steel material is given laser marking treatment with power variations, namely 20 and 60 W. The results of SEM testing will be carried out to obtain data on the results of groove geometry and visibility of the marking results. Furthermore, the AISI 304 stainless steel material from the marking is immersed in corrosive sea water media for a span of 60, 90 and 120 days to measure the corrosion rate that occurs. As a result, the AISI 304 stainless steel marking material is also subjected to SEM observation to determine the type of corrosion and surface morphology of the laser marking results due to the influence of corrosion that occurs. It is expected that the results of this study will be able to provide recommendations for work process parameters in laser marking that can be applied to spoon and fork products as optimal parameters for improving the quality of better marking results.